2014
DOI: 10.5573/jsts.2014.14.5.666
|View full text |Cite
|
Sign up to set email alerts
|

High Performance p-type SnO thin-film Transistor with SiOxGate Insulator Deposited by Low-Temperature PECVD Method

Abstract: We have investigated the gate insulator effects on the electrical performance of p-type tin monoxide (SnO) thin-film transistors (TFTs). Various SnO TFTs are fabricated with different gate insulators of a thermal SiO 2 , a plasma-enhanced chemical vapor deposition (PECVD) SiN x , a 150 o Cdeposited PEVCD SiO x , and a 300 o C-deposited PECVD SiO x . Among the devices, the one with the 150 o C-deposited PEVCD SiO x exhibits the best electrical performance including a high field-effect mobility (=4.86 cm 2 /Vs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…20) The previous finding is reproduced in Fig. 3(a) and, according to the analysis performed in the previous work, the evolution of the device's operation behavior can be divided into three stages: (i) Prior to the annealing, the channel film is a Sn-dominant metallic phase of the n-type with plenty of electrons (>10 22) They showed that, after annealing, the XRD spectrum of the film on thermal SiO 2 exhibited polycrystalline SnO peaks but none were seen for the film on PECVD-oxide. Owing to the low deposition temperature (150 °C), it was found that the PECVD-oxide was porous in structure and, accordingly, the morphology of the deposited oxide was very rough compared with that of the thermal oxide.…”
Section: Effects Of Gate Dielectrics On Crystallization Processmentioning
confidence: 57%
See 1 more Smart Citation
“…20) The previous finding is reproduced in Fig. 3(a) and, according to the analysis performed in the previous work, the evolution of the device's operation behavior can be divided into three stages: (i) Prior to the annealing, the channel film is a Sn-dominant metallic phase of the n-type with plenty of electrons (>10 22) They showed that, after annealing, the XRD spectrum of the film on thermal SiO 2 exhibited polycrystalline SnO peaks but none were seen for the film on PECVD-oxide. Owing to the low deposition temperature (150 °C), it was found that the PECVD-oxide was porous in structure and, accordingly, the morphology of the deposited oxide was very rough compared with that of the thermal oxide.…”
Section: Effects Of Gate Dielectrics On Crystallization Processmentioning
confidence: 57%
“…21) To date, there is only one paper reporting the effect of the underlying gate dielectric (SiO 2 ) deposited with various tools on the characteristics of SnO thin-film transistors (TFTs). 22) In this work, for the first time, we show that the gate dielectric materials may impact the transformation of the structure of the tin-oxide channel film during the oxygen annealing. Various annealing schemes were designed and conducted to gain insights into the evolution of film properties with thermal annealing and understand the consequences on device performance.…”
Section: Introductionmentioning
confidence: 75%